Transit justice: community perceptions and anticipations of a new light rail transit line in Prince George's County, Maryland, United States - Wu, Shuling; Roberts, Jennifer D. (Cities & health, 2023)
Transit-oriented developments are increasingly important as they address many modern urban environment problems such as urban sprawl, pollution, and rising rates of non-communicable diseases. However, their implementation is difficult as cities are complex systems. Urban health improvements is a labyrinthian process as enhancements in one area often leads to several unintended side effects, such as transit-induced gentrification or injustice. The Purple Line Impact on Neighborhood, Health and Transit (PLIGHT) study examines the community impact of a forthcoming light rail train line in Prince George's County, Maryland, a predominantly Black and Hispanic community. Results show that despite mindful planning the Purple light rail train is subject to 'Transit Orientated Development' idealism, which can propagate transit injustices. This qualitative study highlights the disconnect between this idealism and practice. It explicitly identifies the most vulnerable of transit users and highlights how neoliberal urbanism contributes to health inequities in Transit Orientated Development practice.